On the Internal Gas Dynamics and Efficiency of a Vortex Water-Vapor Plasma Generator - Charakhovski, L.; Essiptchouk, A. [UNESP]; Otani, C.; Petraconi, G.; Marquesi, A.; Sauchyn, V.; Khvedchyn, I.; Olenovich, A.; Liavonchyk, A.; Skamarokhau, D.; Halinouski, A. (Springer Nature, 2017)
Results of experimental investigations of a new-type generator of an arc water plasma, having a high thermal efficiency close to 100%, are presented. This generator represents a system comprising a vortex arc plasma generator, in which an electric arc is stabilized by water vapor and a straight-through-flow tubular electric steam generator. Such a high efficiency of the plasma generator system was achieved due to the refinement of the internal gas dynamics of the plasma generator and the heat and mass transfer in its discharge channel as a result of the improvement of the vortex stabilization and thermal insulation of an arc discharge in it by the specially organized ″instantly permeable″ channel wall cooled by only the working water used for generation of the plasma.
Keywords: arc plasma; vortex stabilization; vortex water-vapor plasma generator